Pengembangan Literasi Budaya Dan Kewarganegaraan Di Sekolah Dasar: Studi Kasus Di Pekanbaru - Muhammad Iqroq Kabari; Reka Miftahul Hayati; Sri Wahyu Ningsih; Zidan Dika Dafara; Febrina Dafit (Universitas Palan, 2023)
The development of cultural literacy and citizenship is an important aspect of primary education. This study aims to analyze different approaches to developing cultural literacy and citizenship in four elementary schools located in Pekanbaru. The four schools included in this research are SDN 182, SDN 195, SDN 21, and SDN 180. This research utilizes a qualitative descriptive approach by analyzing data from field observations, interviews with teachers and students, and documentary studies. The findings of the study indicate that these four schools have different approaches to developing cultural literacy and citizenship. SDN 182 adopts a habituation approach by teaching students to sing the national anthem before starting Civic Education lessons and involving them in community service activities. SDN 195 implements a developmental approach by requiring students to serve as flag ceremony officials, memorize the UUD 1945 (Constitution of the Republic of Indonesia), and understand Pancasila (the foundational philosophy of Indonesia). SDN 21 employs a developmental approach to literacy through extracurricular programs held on Saturdays, introducing Indonesian cultures to students. SDN 180 encompasses various aspects, including flag ceremonies, cultural introductions, and organizing dance extracurricular activities. This research provides a deeper understanding of the diverse approaches that can be employed to develop cultural literacy and citizenship in elementary schools. The findings serve as a foundation for schools and relevant stakeholders in designing effective and student-centered learning programs. Additionally, this study offers inspiration for the development of cultural literacy and citizenship at higher levels of education.